Two‐Weight Codes and Second Order Recurrences. Issue 6 (1st November 2019) - Shi, Minjia; Zhang, Zhongyi; Solé, Patrick
Abstract : Cyclic codes of dimension 2 over a finite field are shown to have at most two nonzero weights. We compute their weight distribution, and give a condition on the roots of their check polynomials for them to be maximum distance separable code.